Evaluation of the Growth Performance of Snails Fed Different Forages under Intensive Management - Odo, B.I.; Orji, A.C. (Pakistan Journal of Nutrition, 2010)
A six-week old experiment was conducted during the early rainy season of the year to investigate the growth performance of snails fed different forages under intensive rearing. The different forages used in the study constituted the treatment groups and they included: Fluted pumpkin (Telferia occidentalis) leaves (TA), African Spinach (Amaranthus sinensis) leaves (TB), Pawpaw (Carica papaya) leaves (TC) and formulated mash (TD). Thirty two (32) snails of 3 weeks old were divided into the four treatment groups of eight (8) snails each in a completely randomized design. Each treatment group was replicated twice. Result of data analysis showed that there was significant difference (p<0.05) in all the parameters studied which included feed intake, weight gain, feed conversion ratio and shell length increase. Feed intake was highest in TA followed by TC and then TD. The highest weight gain recorded in TD differed significantly (p<0.05) with those of TA and TB. There was no statistical difference between TA and TC. Feed conversion ratio was highest in TB followed by TC and least in TD. Shell length increase was significantly lower (p<0.05) in the TB than the other treatment groups that showed no statistical difference with each other. With TA and TC giving the highest weight gain after TD and high overall feed intake, it may be advisable that heliculturists should use fluted pumpkin or Paw paw leaves in intensive snail rearing. Use of formulated ration may only be in time of forage shortages as may be occasioned by seasonal changes.